Straight talk with...Tom Inglesby (Nat Med, 2013)
When letters containing anthrax spores were mailed to several US senators and media offices in September 2001, just one week after the 9/11 attacks, bioterrorism catapulted to the national stage. Political leaders and public health officials, desperate for guidance on this once-theoretical scenario, turned to experts including Tom Inglesby, then deputy director of the Johns Hopkins Center for Civilian Biodefense Strategies, a bioterrorism research and analysis think tank in Baltimore. In the years that followed, Inglesby and his colleagues ran exercises to simulate bioterror incidents, established a peer-reviewed journal on biodefense and advised government agencies on how to reduce the public health impact of biological threats. Today, he continues his work with the think tank, which moved to the University of Pittsburgh Medical Center (UPMC) in 2003 (although it stayed headquartered in Baltimore) and which was recently renamed the UPMC Center for Health Security. As director and chief executive officer for the past four years, Inglesby has expanded the center's focus toward preventing public health crises arising from infectious diseases, pandemics and major natural disasters, in addition to biological, chemical and nuclear accidents or threats. Inglesby spoke with Kevin Jiang about how responses to bioterrorism, pandemics and natural disasters aren't all that different.